Introduction to Blockchain technology. (O'Reilly Media, Inc., 2019)
Blockchain technology is among the most exciting developments in the IT industry in many years. Often shrouded in mystery (including who the person is who developed it), today blockchain is most well known as the technology that underpins cryptocurrencies, the most famous of those being Bitcoin. But blockchain's distributed-ledger technology holds the promise to revolutionize the way businesses and governments create and maintain important records of transactions of all kinds, whether it's contracts, deeds, or any other types of activity for which an inviolable record must be maintained. In this video course, intended for developers and programmers who have a basic understanding of web-based applications, you learn the fundamentals of a blockchain and Decentralized Applications, or DApps, and how data that's stored there is considered immutable--all but impossible to tamper or change, and if an attempt were made, it would be detected immediately. You'll begin by learning blockchain's terminology and then explore how it's used in cryptocurrency. You'll also look at blockchain deployment models, Consensus Algorithms, blockchain supply chain models, DApp modeling and development, as well as development environment requirements for blockchain coding. You'll examine the theory and concepts such as how many distributed computer hosts, called nodes, add bits of information in "chains" of highly encrypted blocks. When you've completed this video course, you'll have a firm understanding of blockchain basics and a solid foundation from which to continue learning and dive deeper into this fascinating field. What you'll learn--and how you can apply it The history of Bitcoin and blockchain technology Technical structure of a Blockchain Basics of how a blockchain works and it architecture Basic understanding of blockchain use cases in business How hashing algorithms work Understand Decentralized Applications, or DApps, architecture and design Migrate centralized database systems into DApps Understand how blockchain manages assets such as cryptocurrencies, and other assets Build an end-to-end transaction flow for blockchain supply chains Basic understanding of cryptography via hands-on exercises The development environment and requirements for blockchain application development This video course is for you because... You want to understand the use cases for blockchain and resources to help get started in the blockchain space You want to "get ahead of the curve" in understanding blockchain technology in general You want to understand where blockchain offers career opportunities You want to apply your knowledge from this course toward your preparation for Certified Hyperledger Fabric Administrator, Certified Hyperledger Sawtooth Administrator, or Certified Hyperledger Fabric Developer certification exam You're interested in pursuing a career as a blockchain security specialist, blockchain Ethereum developer, or blockchain hyperledger developer Prerequisites: Basic understanding of using web-based applications Materials or downloads needed in advance: History and Evolution of Blockchain Technology from Bitcoin Further resources: Comprehensive overview and analysis of blockchain use cases in many industries This article first talk about popular blockchain use cases across industries, including financial, civil services, supply chain, IoT, and healthcare. It will then proceed to a discussion of factors for consideration, before determining proper use cases and developing a successful DApp. Blockchain Decentralized App use case for healthcare data sharing This article looks at one blockchain use case in more detail and talk about steps leading to the implementation of a Decentralized Application or DApp. The use case of healthcare data sharing will be examined further. Intro to Hyperledger Family and Hyperledger Blockchain Ecosystem This article explores Hyperledger blockchain concepts while providing you with the necessary knowledge and important technical design methodology of the Hyperledger ecosystem. Blockchain Quick Start Guide: A beginner's guide to developing enterprise-grade decentralized applications (book).